Ensuring the people’s sovereignty through the constitutional protection mechanism in Vietnam - Tao, Thi Quyen (Đại học Quốc gia Hà Nội, 2020)
In the rule-of-law State, the Constitution is not only the supreme law of the State but also the document expressing the sovereignty of the People. Through the Constitution, the People determine the scope of power assigned to the State. In the practice of exercising power, however, the State may issue unconstitutional documents, commit acts of giving or failing to fulfil the tasks and powers entrusted by the People, thus harming the assuring People’s sovereignty. Therefore, any State needs to protect the Constitution and deals with documents and acts contrary to the Constitution, thereby protecting the sovereignty of the People. The current Vietnam’s Constitution stipulates all the State power belonging to the People and some methods for the People to exercise their power. However, according to the current authors, the constitutional protection activities in Vietnam are not regular and effective because of some following weaknesses such as a lack of specialized constitutional protection agency and spreading legislation on the constitutional protection, overlapping, lack of systemic constitution, lack of mechanism for reviewing and ruling on constitutionality of laws, seemingly advisory measures for protecting the Constitution, recommendations, and low legal validity. Therefore, some documents and acts of the State agencies still violate the People’s sovereignty in Vietnam; many regulations regarding the People’s sovereignty are not guaranteed or implemented in a formal and perfunctory manner. According to the authors of this article, in order to complete the constitutional protection mechanism and ensure the sovereignty of the People in Vietnam, it is necessary to implement these solutions: (i) Innovating thinking, raising awareness of the role and nature of the Constitution, considering the Constitution as a document expressing the People’s sovereignty and having a direct effect; (ii) Implementing constitutional rights of the People to the Constitution; (iii) Establishing a Constitutional Court; (iv) Practicing of direct democratic forms in Vietnam.